Carfilzomib, Lenalidomide, and Dexamethasone In Newly Diagnosed Multiple Myeloma: Initial Results of Phase I/II MMRC Trial - Jakubowiak, Andrzej J; Dytfeld, Dominik; Jagannath, Sundar; Vesole, David H.; Anderson, Tara B.; Nordgren, Brian K.; Lebovic, Daniel; Stockerl-Goldstein, Keith E.; Griffith, Kent A.; Hill, Melissa A.; Harvey, Colleen K.; Dollard, Akari M.; et al. (Blood, 2010)
Abstract 862 Carfilzomib (Cfz) is a novel, irreversible proteasome inhibitor that has demonstrated promising single-agent activity and favorable toxicity profile, including very low rates of peripheral neuropathy and neutropenia in relapsed/refractory multiple myeloma (MM). Combining Cfz with Lenalidomide (Revlimid®, Len), and Dexamethasone (Dex) into CRd shows an additive anti-MM effect in preclinical studies and lack of overlapping toxicity allowing for the use of these agents at full doses and for extended duration of time in relapsed/refractory MM (Niesvizky et al, ASH, 2009). This Phase I/II study was designed to determine the maximum tolerated dose (MTD) of CRd and to assess safety and evaluate efficacy of this combination in newly diagnosed MM. In Phase I, dose escalation follows the TITE-CRM algorithm, with Cfz as the only escalating agent starting at 20 mg/m2 (level 1), maximal planned dose 27 mg/m2 (level 2), and 15 mg/m2, if needed (level -1), given IV on days 1, 2, 8, 9, 15, 16 in 28-day cycles. Len is used at 25 mg PO (days 1–21), and Dex at 40/20 mg PO weekly (cycles 1–4/5-8) for all dose levels. Based on toxicity assessment, the study was amended to add dose level 3 with Cfz at 36 mg/m2 and the number of pts in the Phase I was increased to 35. A total of 36 pts are planned to be treated at the MTD in Phase I/II. Pts who achieve ≥ PR can proceed to stem cell collection (SCC) and autologous stem cell transplant (ASCT) after ≥ 4 cycles, although per protocol design, ASCT candidates are offered to continue CRd treatment after SCC. After completion of 8 cycles, pts receive 28-day maintenance cycles with Cfz (days 1, 2 15, 16), Len days 1–21, and Dex weekly at the doses tolerated at the end of 8 cycles. Responses are assessed by IMWG criteria with the addition of nCR. The study has enrolled 24 pts to date, 4 pts at level 1 (Cfz 20), 14 at level 2 (Cfz 27) and at 6 at level 3 (Cfz 36). Toxicity data are available for 21 pts, of which 19 have completed at least the first cycle required for DLT assessment; 2 pts were removed during the first cycle for events unrelated to study therapy (1 at level 1 and 1 at level 2), and 3 are currently within their first cycle of treatment. There was a single DLT event at dose level 2 (non-febrile neutropenia requiring dose reduction of Len per protocol) and the MTD has not been reached. Hematologic toxicities were reversible and included Grade (G) 3/4 neutropenia in 3 pts, G3/4 thrombocytopenia in 3, and G3 anemia in 2. There have been additional G3 non-hematologic AEs including 1 case of DVT while on ASA prophylaxis, 1 fatigue, 1 mood alteration, and 5 glucose elevations; the last 2 AEs were related to Dex. There was no emergence of peripheral neuropathy (PN), even after prolonged treatment, except in 2 pts who developed G1 sensory PN. Twenty-three pts continue on treatment, most (20 pts) without need for any dose modifications. After a median of 4 (range 1–8) months of treatment, preliminary response rates by IMWG in 19 evaluable pts who completed at least 1 cycle are: 100% ≥ PR, 63% ≥ VGPR, 37% CR/nCR, including 3 pts with sCR. Responses were rapid with 17 of 19 pts achieving PR after 1 cycle and improving responses with continuing therapy in all pts. To date, 7 pts proceeded to SCC using growth factors only, with a median 6.3 × 106 CD34+ cells/kg collected (range 4.1–8.2), after a median of 4 cycles of CRd (range 4–8); all resumed CRd treatment after SCC. After a median of 4 months of follow-up, none of evaluable pts progressed and all are alive. CRd is well tolerated and highly active in newly diagnosed MM with ≥ PR of 100%, including 63% ≥VGPR and 37% CR/nCR. Accrual is ongoing, with updated toxicity and efficacy data to be presented at the meeting. The results of this study represent the first report of treatment of frontline myeloma with Cfz to date, and provide additional support to recently initiated Phase 3 trial of CRd vs. Rd in relapsed MM. Jakubowiak:Bristol-Myers Squibb: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees; Exelixis: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees; Centocor OrthoBiotech: Consultancy, Honoraria, Speakers Bureau; Celgene: Consultancy, Honoraria, Speakers Bureau; Millennium: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees. Off Label Use: Lenalidomide for newly diagnosed multiple myeloma. Jagannath:Millennium: Honoraria; OrthoBiotech (Canada): Honoraria; Celgene: Honoraria; Merck: Honoraria; Onyx Pharmaceuticals: Honoraria; Proteolix, Inc: Honoraria; Imedex: Speakers Bureau; Medicom World Wide: Speakers Bureau; Optum Health Education: Speakers Bureau; PER Group: Speakers Bureau. Vesole:Celgene: Membership on an entity's Board of Directors or advisory committees, Speakers Bureau. Anderson:Millennium: Honoraria, Speakers Bureau; Celgene: Honoraria, Speakers Bureau. Stockerl-Goldstein:Celgene: Speakers Bureau; Millennium: Speakers Bureau. Barrickman:Celgene: Employment, Equity Ownership. Kauffman:Onyx Pharmaceuticals: Employment, Equity Ownership. Vij:Proteolix: Consultancy; Celgene: Membership on an entity's Board of Directors or advisory committees, Research Funding, Speakers Bureau; Onyx: Membership on an entity's Board of Directors or advisory committees, Speakers Bureau.